Melanopsin Retinal Ganglion Cells: relevance to circadian rhythms and sleep in neurodegeneration - La Morgia, Chiara <1977> (Alma Mater Studiorum - Università di Bologna, 2012)
In this PhD thesis 3 projects were addressed focusing on the melanopsin retinal ganglion cells (mRGCs) system and its relevance for circadian rhythms and sleep in neurodegeneration. The first project was aimed at completing the characterization of mRGCs system in hereditary optic neuropathies (LHON and DOA). We confirmed that mRGCs are relatively spared also in post-mortem retinal specimens of a DOA case and pupillometric evaluation of LHON patients showed preservation of the pupillary light reflex, with attenuated responses compared to controls. Cell studies failed to indicate a protective role exerted by melanopsin itself. The second project was aimed at characterizing the possible occurrence of optic neuropathy and rest-activity circadian rhythm dysfunction in Alzheimer (AD) and Parkinson disease (PD), as well as, at histological level, the possible involvement of mRGCs in AD. OCT studies demonstrated a subclinical optic neuropathy in both AD and PD patients, with a different pattern involving the superior and nasal quadrants in AD and the temporal quadrant in PD. Actigraphic studies demonstrated a tendency towards an increased intradaily variability (IV) and reduced relative amplitude (RA) of rest-activity circadian rhythm in AD and a significant increased IV a reduced RA in PD. Immunohistochemical analysis of post-mortem retinal specimens and optic nerve cross-sections of neuropathologically confirmed AD cases demonstrated a significant loss of mRGCs and a nearly significant loss of axons in AD compared to controls. The mRGCs were affected in AD independently from age and magnitude of axonal loss. Overall these results suggest a role of the mRGCs system in the pathogenesis of circadian dysfunction in AD. The third project was aimed at evaluating the possible association between a single nucleotide polymorphism of the OPN4 gene and chronotype or SAD, failing to find any significant association with chronotype, but showing a non-significant increment of TT genotype in SAD.